2014
DOI: 10.1016/j.freeradbiomed.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 2 activates an antioxidant pathway to promote the survival of cells with mitochondrial dysfunction

Abstract: We previously reported that Polo-like kinase 2 (PLK2) is highly expressed in cells with defective mitochondrial respiration and is essential for their survival. Although PLK2 has been widely studied as a cell cycle regulator, we have uncovered an antioxidant function for this kinase that activates the GSK3-NRF2 signaling pathway. Here, we report that the expression of PLK2 is responsive to oxidative stress and that PLK2 mediates antioxidant signaling by phosphorylating GSK3, thereby promoting the nuclear trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…Homeostatic adaptation of the cell to external stress is mainly controlled by p53 target genes (37,38). A set of p53dependent genes such as Plk2 and p21 cip1 are activated by DNA damage, protecting cells from injury (25,(37)(38)(39)(40). Another set of p53-dependent genes such as BCL2 associated X (Bax), apoptosis regulator, P53 up-regulated modulator of apoptosis (Puma), and phorbol-12-myristate-13-acetate-induced protein 1 (Noxa) execute apoptosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…Homeostatic adaptation of the cell to external stress is mainly controlled by p53 target genes (37,38). A set of p53dependent genes such as Plk2 and p21 cip1 are activated by DNA damage, protecting cells from injury (25,(37)(38)(39)(40). Another set of p53-dependent genes such as BCL2 associated X (Bax), apoptosis regulator, P53 up-regulated modulator of apoptosis (Puma), and phorbol-12-myristate-13-acetate-induced protein 1 (Noxa) execute apoptosis (41).…”
Section: Discussionmentioning
confidence: 99%
“…Plk2, Plk3, and Plk5. Plks 2, 3, and 5 have been described as immediate early response genes since the expression of these three kinases increases upon DNA damage and oxidative stress [30][31][32][33][34][35]. This, in turn, leads to the activation of the G2/M checkpoint in a p53-dependent manner [36][37][38][39][40].…”
Section: The Plk Family: Expression Localization and Cellular Functmentioning
confidence: 99%
“…We previously reported that PLK2 mediates defective mitochondrial changes and PLK2 activity is required for cell survival 20,21 . To investigate whether PLK2 is altered in DKD tissues, we performed the microarray and GSEA analysis.…”
Section: Resultsmentioning
confidence: 99%